1978
DOI: 10.1136/thx.33.5.569
|View full text |Cite
|
Sign up to set email alerts
|

The anti-reflux mechanism after cardiomyotomy.

Abstract: M (1978). Thorax, 33,[569][570][571][572][573]. The anti-reflux mechanism after cardiomyotomy. Only 18 of 83 patients who had had a cardiomyotomy for achalasia could be induced to reflux barium. Mucosal herniation through the myotomy was shown in most by radiography. Perfusion manometry showed a higher pressure zone in the oesophagogastric junction region in 22 of 24 patients studied. This high pressure zone responded to an increment in abdominal pressure by a greater increment. The same response was seen in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Symptomatic gastroesophageal reflux occurs frequently after cardiomyotomy. 27,28 Antireflux surgical procedures are frequently performed at the same time as cardiomyotomy, especially when an abdominal route is used for the operation. 29 In our study, symptomatic gastroesophageal reflux was seen in only 4% of patients following dilatation and resolved spontaneously in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…Symptomatic gastroesophageal reflux occurs frequently after cardiomyotomy. 27,28 Antireflux surgical procedures are frequently performed at the same time as cardiomyotomy, especially when an abdominal route is used for the operation. 29 In our study, symptomatic gastroesophageal reflux was seen in only 4% of patients following dilatation and resolved spontaneously in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…The Mayo Clinic study in dogs suggested that reflux was more likely if a long myotomy was done (Ellis et al 1967), though Effier et al (1971, who routinely used a long incision, reported an incidence of reflux little higher than that at the Mayo Clinic. It has even been suggested that the gastro-oesophageal junction does not remain functional after cardiomyotomy and that competence of the cardia is maintained by other factors (Ellis et al 1967, Lobello et al 1978. Reflux causing heartburn is a considerable nuisance to a patient after cardiomyotomy, and responds poorly to medical therapy.…”
Section: Surgerymentioning
confidence: 99%
“…Such strictures are serious, for they respond poorly to medical therapy and bougienage, and while bile diversion operations may help (Holt & Large 1961), total oesophageal replacement may be necessary. Several series of surgical treatment show a sufficiently greater likelihood of subsequent reflux to render the results unsatisfactoryyet other series report no reflux problem, without any clear reason (though Lobello et al (1978) believe that careful preservation of 'the hiatal mechanism' is the reason). Stricture must be regarded as the most serious long-term consequence of therapy.…”
Section: Pneunatic Dilatorsmentioning
confidence: 99%
“…The efficacy of these valve-building operative techniques in the treatment of esophagitis is well established. Discussion continues concerning the results, and their efficacy in controlling the potential reflux diseases that are primarily characterized by disturbed motility, such as achalasia [3,11]. Controversy also exists about the danger of obstructive dysphagia after cardiomyotomy associated with antireflux surgery [12].…”
mentioning
confidence: 99%